Análise de licenças médicas de professores de ensino municipal público - Pacheco, Daniela Ignacio (2015)
Previous studies show that the teacher s ailments may result from biological origins related to the work environment or its organization. Speech-Language Pathologists have been studying not only the disorders related to the voice, but the ones with musculoskeletal, psychic and vascular origins that we might find among teachers. Objetives: to analyse the medical leaves of teachers from a public school district and to associate the variables age, gender and disease type that determined the leave (ICD-10). Method: this study is retrospective and transversal. The data was provided by the Human Resources Department school district of a city that belongs to São Paulo s county. The medical leaves of teachers who were working registered in the period between march 2007 and may 2013 were analyzed. From the data we studied, the variables age, gender and disease type that determined the leave (ICD-10). We don t have data related to the levels that those teachers work with. Results: 1.801 leaves were registered among 327 teachers. The finds show similar distribution related to the gender. The age average was 39,6 years (20,4 to 61,6 years old). The average time between admission and the first leave was 39,1 months (0,20 and 217,8 months), totalizing 4.775 days. The total time on average sickness absence was 14,6 days (1 and 147). The illness that most determined leaves were those of respiratory system, digestive system disorders, infectious and parasitic diseases, musculoskeletal and conjunctive tissues, according to the International Classification of Diseases (ICD-10). The findings didn t show significant statistic difference comparing those leaves according to gender and age. The infectious and parasitic diseases, musculoskeletal and the factors that influentiate the general health were more frequent in the first semester. Conclusion: The 1.801 medical leaves analysis of 327 teachers, didn t show significant association related to the variables gender and age. The leaves (the majority medical certificates) presented in larger number related to the respiratory and digestive system disorders, infectious and parasitic diseases, musculoskeletal and conjunctive tissues, according to the International Classification of Diseases (ICD-10)